Self-medication in the context of COVID-19, the dangers of the practice and associated factors (Research, Society and Development, 2023)
Introduction: With the advancement of the COVID-19 pandemic, many people sought treatment or prevention alternatives for the disease and adhered to self-medication, without taking into account the possible risks of this practice. Objective: To characterize the practice of self-medication in the context of the COVID-19 pandemic, it’s dangers and associated factors. Methodology: An integrative literature review was carried out, with searches in the Virtual Health Library (VHL) databases, using the following Health Sciences Descriptors (DeCS): “COVID-19” and “self-medication” and the Boolean operator “AND”, searching for full articles published free of charge in the last five years in English, Portuguese or Spanish. A total of 57 articles were found, of which 10 were selected for full reading in order to answer the following guiding question: “What are the dangers, associated factors and characteristics of self-medication during the COVID-19 pandemic?”. Results: Self-medication was practiced by, on average, one third of the population during the pandemic. Health professionals, medical students and women self-medicated more compared to the rest of the population. The most used medications were antibiotics, ivermectin, antimalarials, NSAIDs and paracetamol, in addition to dietary supplements such as zinc, vitamin C and multivitamin complexes. Study participants had easy access to these medications. Traditional therapies have also been reported. Conclusion: Self-medication was very present, with heterogeneous characteristics of population distribution. Most medications were used without indication, and some may pose considerable health risks. More studies need to be carried out on the subject.